INTRODUCTION TO SPECIAL ISSUE: “YOUTH TRANSITIONS TO EDUCATION AND EMPLOYMENT: A MOBILITIES PERSPECTIVE” - Smith, Angèle; Power, Nicole (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
This special issue focuses on the geographical and spatialized mobilities related to youth transitions to post-secondary education and employment. The “mobility turn” in social sciences in the last decade recognizes that life is increasingly organized and shaped by mobilities (and immobilities) across varying spatial and temporal scales. Yet these mobilities have only recently been examined and theorized as central to understanding the complexity and diversity of young people’s experiences. The collection of articles in this special issue presents a multiplicity of young people’s relationships to mobilities, particularly as they pursue post-secondary education and employment. The papers are concerned with: (a) the motivations for and expectations of imagined mobility (the innumerable reasons why youth choose, or are compelled, to move or stay), whether focused on the outmigration or inmigration of mobile youth; (b) the lived experiences that youth have in their mobility practices (focusing on multistranded relationships between places of origin and destination, or recognizing the temporality of that mobility); and (c) the value that these youth mobility studies have for policy issues and policy recommendations. The papers in this issue are case studies concerned with youth mobility prior to the COVID-19 pandemic. They use qualitative and quantitative methods, representing inter- and cross-disciplinary approaches from anthropology, sociology, education, communication, and rural development studies. They derive from a collaboration through the On the Move Partnership, an 8-year interdisciplinary research initiative with a key focus on young people’s employment- and education-related geographical mobilities in Canada.